A pilot, four-week, dietary program with targeted nutraceuticals improves cardiometabolic functioning, metabolic transformation, and gut health - Wei Gao; Joseph J. Lamb; David Graham; Bhargavi Manda; Clinton J. Dahlberg; E. Wesley Huff; Michael Saunders; Matthew L. Tripp (Journal of Functional Foods)
Exposure to environmental pollutants increases the risk for metabolic dysfunction. Dietary and lifestyle interventions may reduce the risks associated with this toxicity. We conducted this 4-week, observational, clinical study to explore the safety and efficacy of a proprietary dietary program formulated to enhance cardiometabolic functioning, metabolic transformation, and gut health. Thirty-eight generally healthy overweight subjects were assigned a low-glycemic load, Mediterranean-style food plan with targeted nutraceutical supplementation and a physical activity regimen. Subjects expressed positive subjective health and symptom changes coincident with improvements in anthropomorphic variables, lipid profiles, glycemic measures, vascular biomarkers, cardiovascular risk, systemic inflammation, hepatic function, urinary heavy metal excretion, and gut health. Thus combining targeted nutraceutical supplementation with a low-glycemic load food plan and exercise may represent a novel nutritional approach to improving the body's ability to modulate the toxicity of pollutants and reducing cardiometabolic risk factors in generally healthy overweight persons.